The Effectiveness of Rome Beauty Apple Peel Extract (Malus sylvestris Mill) on the Growth of Salmonella Typhi - Gaffar, Herry Darsim; Hasan, Yuliono Trika Nur; Aprilia, Nike (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Salmonella typhi is an illness caused by the bacterium Salmonella typhi (abbreviated S. typhi). It may affect people of all ages, but is most prevalent in young people. At the moment, there is widespread resistance to chloramphenicol as the first-line antibiotic for S. typhi infection, necessitating the development of new treatments based on natural components. AIM: The purpose of this research is to investigate the efficacy of Rome Beauty apple peel extract, which is believed to possess antibacterial properties capable of inhibiting the development of S. typhi bacteria. METHODS: To determine the Minimum Inhibitory Concentration (MIC) and Minimum Kill Concentration (MKC) for antibacterial activity using disc diffusion and tube dilution methods, with nine treatments of Rome Beauty apple peel extract at concentrations of 50%, 25%, 12.5 %, 6.25%, 3.125%, 1.56%, and 0.78%, as well as a positive control (chloramphenicol 30 mg/ml) (aquadest). SPSS is used to analyze data. RESULTS: The findings of this investigation established a 12.5 % MIC with an average diameter of the inhibition zone of 13.67 mm and a 50% MKC with an average number of bacterial colonies of 22.33 CFU/mL. The Kruskal-Wallis test was used to examine the MKC data (significance p = 0.002) and the One-Way ANOVA test was used to study the MIC data (significance p = 0.001). CONCLUSION: The research concluded that Rome Beauty apple peel extract inhibited the development of S. typhi bacteria. 67 mm and 50% MKC with an average number of bacterial colonies of 22.33 CFU/mL. The Kruskal-Wallis test was used to examine the KHM data (significance p = 0.002) and the One-Way ANOVA test was used to study the MIC data (significance p = 0.001). The research concluded that Rome Beauty apple peel extract inhibited the development of S. typhi bacteria. 67 mm and 50% MKC with an average number of bacterial colonies of 22.33 CFU/mL. The Kruskal-Wallis test was used to examine the MKC data (significance p = 0.002) and the One-Way ANOVA test was used to study the MIC data (significance p = 0.001). The research concluded that Rome Beauty apple peel extract inhibited the development of S. typhi bacteria.